2018
DOI: 10.1044/2017_jslhr-l-17-0246
|View full text |Cite
|
Sign up to set email alerts
|

Planning Deficits in Children With Specific Language Impairment Are Reflected in Unnecessarily Awkward Grasps

Abstract: We suggest that this perseverative behavior is indicative of a domain-general problem in planning in SLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…This result was partly in line with earlier research findings on children with DLD (Sanjeevan et al., 2018). In their study, children with DLD did not differ from peers in the use of ESC grasps in target trials requiring turning the dowel.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result was partly in line with earlier research findings on children with DLD (Sanjeevan et al., 2018). In their study, children with DLD did not differ from peers in the use of ESC grasps in target trials requiring turning the dowel.…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation for the difference between this study and Sanjeevan et al. (2018) was that our study included relatively few children clinically identified as having DLD. Sanjeevan et al.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations